Identification of novel α7 nicotinic receptor ligands by in silico screening against the crystal structure of a chimeric α7 receptor ligand binding domain. - AKDEMİR, ATİLLA; THOMPSON, AJ; de, Graaf; Akdemir, ATİLLA; de, Esch; KOOISTRA, AJ; EDINK, E; LUMMIS, SC (My University, 2012)
A hierarchical in silico screening procedure using the crystal structure of an agonist bound chimeric α7/Ls-AChBP protein was successfully applied to both proprietary and commercial databases containing drug-like molecules. An overall hit rate of 26% (pK(i) ≥5.0) was obtained, with an even better hit rate of 35% for the commercial compound collection. Structurally novel and diverse ligands were identified. Binding studies with [(3)H]epibatidine on chimeric α7/5-HT(3) receptors yielded submicromolar inhibition constants for identified hits. Compared to a previous screening procedure that utilized the wild type Ls-AChBP crystal structure, the current study shows that the recently obtained α7/Ls-AChBP chimeric protein crystal structure is a better template for the identification of novel α7 receptor ligands.
Keywords: α7